The innofusion of electronic banking in Indonesia - Nofie Iman (The University of Manchester, Manchester Business School, 2011)
Even though financial innovation plays an important role in the modern economy, surprisingly there have been few empirical literatures. In developing countries, electronic banking (e-banking), for example, received relatively little attention although has been deployed for years. Indonesia presents unique case of Asian tiger economies, especially after experiencing crisis, financial recession, and economic reform. This research address how e-banking being developed in Indonesia, how it diffused from time to time, what factors that drives and influences the e-banking implementation, how banks manage their e-banking, and what lessons can we learn from it. This study concludes by summarising the case of innofusion of electronic banking in Indonesia. Customers and competitors play an important role in influencing e-banking services adoption. There is also an indication that bigger and older banks are not as innovative and dynamic as their smaller and newer peers. Interestingly, the unavailability of legal protection does not discourage them to partner and cooperate with each other and probably true that it is only 'those' people who drive innovation among Indonesian banks.
Keywords: 330; innofusion; diffusion of innovation; electronic banking; financial services